Validation of SUV thresholds in (¹⁸F)SiTATE PET/CT for accurate meningioma segmentation - Mansour, Nabeel; Joram, Julian; Grawe, Freba; Hinterberger, Anna; Rübenthaler, Johannes; Klambauer, Konstantin; Kunz, Wolfgang G.; Winkelmann, Michael; Cyran, Clemens C.; Ricke, Jens; Öcal, Osman; Unterrainer, Marcus; et al. (European journal of nuclear medicine and molecular imaging, 2025)
Purpose Somatostatin receptor (SSTR)-targeted PET/CT provides valuable clinical insights beyond standard imaging in meningioma patients. Due to its excellent diagnostic capabilities and favorable logistics, the 18F-labeled SSTR-targeting peptide SiTATE is increasingly in demand. We aimed to validate a recently proposed standard uptake value (SUV) threshold for accurate meningioma delineation in a clinically diverse patient cohort, including complex anatomical locations and lesions with prior surgical intervention. Methods Consecutive patients with known or suspected meningioma who underwent [18F]SiTATE PET/CT and contrast enhanced cerebral MRI were included. Lesions were semi-automatically segmented on PET images using an individualized minimal SUV (SUVmin) within a manually defined volume of interest. Correlative CT and MRI images were used to refine segmentations for each lesion, identifying the optimal lesion-specific SUVmin to accurately capture the true volume of the meningioma. All lesions were additionally segmented using the recently proposed threshold of 4.0, and resulting volumes were compared. Results 61 patients with 109 lesions were analyzed: 40 (37%) extraosseous, 32 (29%) partial trans-osseous, and 37 (34%) predominantly intraosseous. The median optimal SUVmin for lesion delineation was 4.2. Osseous involvement did not significantly affect the median SUVmin (p = 0.1). Individualized SUV volumes showed excellent absolute agreement with those obtained using the fixed threshold of 4.0 (ICC[A,1] = 0.967; 95% CI: 0.952-0.977; p < 0.0001). However, 17 lesions (SUVmax < 4.2) were not captured by the fixed threshold. Conclusion The proposed SUV threshold of 4.0 showed promising results, supporting its suitability for clinical practice. Although limitations were evident, with 16% of lesions — primarily very small — showing reduced uptake and therefore not captured by this threshold, the study underscores its applicability in clinical practice.